2009
DOI: 10.1007/s12094-009-0439-2
|View full text |Cite
|
Sign up to set email alerts
|

High-dose-rate (HDR) plesiotherapy with custom-made moulds for the treatment of non-melanoma skin cancer

Abstract: This modality of treatment offers an alternative for those patients not candidates for surgical procedures because of medical contraindications or risk of disfigurement or functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…In fact, during HDR-BT, the dose remains on the surface and does not penetrate deeply with optimal sparing of normal tissues due to dose concentration into the clinical target volumes (CTV) and rapid dose fall-off at target periphery [10, 11, 12, 13, 14, 15, 16, 17]. Published studies have mainly reported standard fractionation and hypofractionated brachytherapy regimens in patients treated with HDR-BT, and the biological effective dose (BED) was often calculated due to define the total dose and dose for fractions regimen for a better local control and acceptable late and acute toxicity [19, 20, 21, 22, 23, 24, 25, 26, 33, 34, 35, 36, 37]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, during HDR-BT, the dose remains on the surface and does not penetrate deeply with optimal sparing of normal tissues due to dose concentration into the clinical target volumes (CTV) and rapid dose fall-off at target periphery [10, 11, 12, 13, 14, 15, 16, 17]. Published studies have mainly reported standard fractionation and hypofractionated brachytherapy regimens in patients treated with HDR-BT, and the biological effective dose (BED) was often calculated due to define the total dose and dose for fractions regimen for a better local control and acceptable late and acute toxicity [19, 20, 21, 22, 23, 24, 25, 26, 33, 34, 35, 36, 37]. …”
Section: Resultsmentioning
confidence: 99%
“…The development of new devices for small skin tumor treatment and the introduction of commercial electronic BT have attracted considerable interest for BT as a skin cancer treatment. Despite the new technologies available, few studies have focused on the treatment of NMSC with HDR-BT and hypofractionated regimes seems to be a valid option for the treatment of NMSC with very good local control, toxicity, and cosmetic result [19, 20, 21, 22, 23, 24, 25, 26, 32, 33, 34, 35, 36, 37, 43, 44]. In 1999, Köhler-Brock et al .…”
Section: Discussionmentioning
confidence: 99%
“…Lowcost 3D printers are a promising solution for the customization of the HDR BT applicators but regulatory materials' approval is required for clinical application [13]. Published studies involving mould technique have shown good local control and cosmesis [14][15][16][17][18][19][20] (see separate file for table).…”
Section: Surface Mouldsmentioning
confidence: 99%
“…When using contact BT, the schedule is similar to electron beam, and 3-5 Gy per fraction 2-3 days per week in 4-5 weeks is effective [16]. In large areas such as scalp, 2-3 Gy per day fractionation is preferable [83][84][85].…”
Section: Brachytherapy Doses and Fractionationmentioning
confidence: 99%
“…Our technique of HDR plesiotherapy based upon custommade molds has been previously described. 13 Briefly, personalized molds consist of a flexible pad of silicone rubber, 10 mm thick, with a customizable array of 6F plastic catheters embedded separated by 1 cm that easily conforms to the shape of surfaces. The number of plastic tubes and the separation between them depended on the size of the area to be treated.…”
Section: Case Reportmentioning
confidence: 99%